Design of an Ergonomic Prototype for Oil Palm Harvesting and Post-Harvesting Aid to Reduce the Risk of Musculoskeletal Disorders - Sukapto, Paulus; Prakoso, Dito; Paruhum, Matthew R; Winata, Sally F (Ann Publisher, 2025)
Background. Oil palm harvesting has many steps until the oil palm fruit can be distributed to the next stage. It began with cutting oil palm fronds using egrek aids, picking up oil palm with a corner tool, and transporting it with angkong aids. Aims. Blind prototype of egrek, tojok, and angkong aids in reducing cases of Musculoskeletal Disorders (MSDs) that occur in workers. Method. The measurement method of MSDs with the Nordic Body Map and Rapid Entire Body Assessment (REBA). Prototype design with literature study and prototyping practices. Result. Modified Egrek tools, designed by the researcher, can make it easier for harvesters to cut palm fronds. The results of this tool repair are able to reduce the REBA value. The corner aid enables the operator to avoid making sudden movements to withstand the mass load of fresh fruit bunches (FFB), thereby reducing the risk of MSDs interference. Ankle aids reduce the risk of injury to the wrist because they push heavy loads. Conclusion. Prototypes of egrek, tojok, and angkong aids have succeeded in reducing the risk of MSDs in oil palm harvesting.